ANALISIS NILAI KERUSAKAN DAN PRIORITAS PERBAIKAN JALAN PADA LAPISAN PERMUKAAN KAKU MENGGUNAKAN METODE PCI - lenahatu, Jermias ravi; Anggreni, Ida Ayu Ari (Civil Infrastructure Engineering and Architectural Design, 2018)
Road is an infrastructure in support of the economic rate and play a very big role in the progress and development of a region. With the increasing age of roads and roads continuously experiencing the stresses due to traffic loads borne from the initial conditions of the pavement design, the ability of road services will decrease further. Therefore, research is needed to identify road damage in 5 secondary arterial roads of Depok City, West Java. This study aims to determine the condition of roads and the determination of road maintenance priority in 5 secondary arterial roads Depok City. This research uses Pavement Condition Index method (PCI) which is used to know the condition of road and Analytical Hierarchy Process (AHP) method to determine the order of prirotas of road maintenance. The criteria used for decision making are budget, road condition, LHR, regional development and economy. Result of research by PCI method, from 5 road segment, it is found that the most damaged road is Jalan Merawan with PCI value is 23 (Serious). For the determination of road maintenance criteria by AHP method resulted in the criterion of road condition as the highest criterion with a weight of 0,505. From the assessment of each criteria on the 5 road segments found that Access UI access road becomes the first priority with the weight of 0.242.Keywords: AHP, Road Condition, PCI, Priority setting.